132k views
0 votes
Find the simplified product b-5/2b x b^2+3b/b-5

2 Answers

3 votes

Your answer should be A

Find the simplified product b-5/2b x b^2+3b/b-5-example-1
User Nvrtd Frst
by
6.1k points
7 votes

Answer:

The product
(b-5)/(2b)*(b^2+3b)/(b-5)=(b+3)/(2)

Explanation:

Given expression
(b-5)/(2b) and
(b^2+3b)/(b-5)

We have to find the product of
(b-5)/(2b)*(b^2+3b)/(b-5)

Consider the given expression
(b-5)/(2b)*(b^2+3b)/(b-5)

Multiply fractions, we have,


(a)/(b)\cdot (c)/(d)=(a\:\cdot \:c)/(b\:\cdot \:d)


=(\left(b-5\right)\left(b^2+3b\right))/(2b\left(b-5\right))

Cancel common factor ( b - 5 )

we have,
=(b^2+3b)/(2b)

Apply exponent rule,


\:a^(b+c)=a^ba^c


b^2=bb


=bb+3b=b(b+3)


=(b\left(b+3\right))/(2b)

Cancel common factor b , we have,


=(b+3)/(2)

Thus, the product
(b-5)/(2b)*(b^2+3b)/(b-5)=(b+3)/(2)

User Filip Kraus
by
6.2k points